A quasi-experimental study of form-focused instruction at Hanoi University of Industrial Fine Arts - Nguyễn, Thị Thịnh (ĐHNN, 2017)
Chapter 1- Introduction: Firstly, this chapter presents the rationale for conducting the study. This part then will be followed by the aim of the study, research questions, significance, the scope of the study. Finally, the structure of the study will be presented so that the reader will have an overall look of order of the study. Chapter 2 - Literature review: This chapter deals with an overview of the literature. It starts with the definition of terminologies including grammatical competence and FFI. It is then concerned with FonFvs. FonFs. Next part is about the advantages and disadvantages of FFI. Chapter 3 - The study: This chapter presents the research design, research procedures, and the result of the study. Chapter 4 - Conclusion: This chapter includes the summary of the main findings, the conclusions, the recommendations, and the limitations and the suggestions for future studies. .